Exercise-Induced Abnormalities of Regional Myocardial Deformation in Anomalous Aortic Origin of the Right Coronary Artery. Issue 6 (November 2020) - Binka, Edem; Zhao, Ni; Wood, Scott; Zimmerman, Stefan L.; Thompson, W. Reid
Aims: Congenital coronary artery anomalies are uncommon and may result in sudden death. Management of asymptomatic patients with anomalous aortic origin of the right coronary artery (AAORCA) remains controversial with a lack of evidence to guide decision-making. We hypothesized that patients with AAORCA may have exercise-inducible ischemia detectable as abnormalities in regional myocardial deformation on exercise stress echocardiography (ESE). Methods: We reviewed clinical data, computed tomography angiography, and treadmill ESE from 33 AAORCA patients (21 unoperated, 12 operated) and 11 controls. Regional wall motion on ESE was visually assessed. Doppler tissue imaging was done pre and post exercise to evaluate regional myocardial wall deformation. The post- to pre-exercise time to peak systolic strain corrected for heart rate ratio (TPScR) for the left ventricular inferior and anterior walls of AAORCA patients was compared to controls. Results: No regional wall motion abnormalities were noted. The TPScR of the inferior wall was higher in unoperated (0.96 ± 0.41) but not operated (0.84 ± 0.28) AAORCA patients compared to controls (0.76 ± 0.18, P = .03 vs .23, respectively). There was no significant difference in TPScR of the anterior wall between unoperated patients and controls ( P = .08). Conclusion: In some AAORCA patients undergoing ESE, TPScR of the left ventricular inferior wall is elevated, suggestive of ischemia induced by exercise in myocardium supplied by the right coronary artery. Further work is needed to understand the potential role of this finding in risk assessment.